2019
DOI: 10.1080/02656736.2019.1648886
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic radiofrequency ablation of subcardiac hepatocellular carcinoma: a case-control study

Abstract: Purpose: The purpose of this study is to evaluate the safety and efficacy of stereotactic radiofrequency ablation (SRFA) for the treatment of subcardiac hepatocellular carcinoma (HCC). Material and methods: From 2003 to 2018, 79 consecutive patients underwent 104 multi-probe SRFA sessions for the treatment of 114 subcardiac HCC with a median size of 2.5 cm (0.5-9.5 cm). The results were compared with a randomly selected control group of 79 patients with 242 HCC with a median size of 2.0 cm (0.5-12 cm) followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
(42 reference statements)
0
20
0
Order By: Relevance
“…The method of SRFA has been reported in detail previously [16][17][18]. An example SRFA for BCLM is shown in Fig.…”
Section: Srfa Proceduresmentioning
confidence: 99%
“…The method of SRFA has been reported in detail previously [16][17][18]. An example SRFA for BCLM is shown in Fig.…”
Section: Srfa Proceduresmentioning
confidence: 99%
“…All of the 34 included works were single-centre studies, of which 26 were retrospective studies (29,30,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)31,(49)(50)(51)(52)(53)(54)(32)(33)(34)(35)(36)(37)(38), 3 prospective case series(55-57), 3 prospective cohort studies(58-60) and 2 randomised controlled trials (61,62). Two studies reported results using a laparoscopic treatment access (44,55), the other 32 reporting on thermal ablations using a percutaneous approach.…”
Section: Resultsmentioning
confidence: 99%
“…Four propensity score matched analyses compared stereotactic thermal ablation for different subtypes of patients or lesions. Stereotactic RFA yielded similar safety and treatment e cacy outcomes when comparing CT 'invisible' tumours ablated with MR image fusion to CT visible tumours (30), octogenarians to a younger study population (36), lesions in a subphrenic location to non-dome locations (39) and HCC in a subcardiac position to a non-subcardiac location (40).…”
Section: Comparative Studiesmentioning
confidence: 90%
“…The method of SRFA has previously been reported in detail [20][21][22] . In brief, the whole treatment is performed under general anesthesia with muscle paralysis.…”
Section: Methodsmentioning
confidence: 99%